Odpowiedź :
1/3x+2=x
1/3x-x=-2
-2/3x=-2
x=3
b)-14x-7=4
-14x=11
x=-11/14
c)-3/4x=2/4
x=-2/3
zad2
a)
-45x-3x≥-9
-48x-3x≥-9
x≤9/48
b) 5x>0
c) -0,3x-0,6-0,6+0,9>0,1x
-0,4x>0,3
x>0,3: (-o,4)
x>-0,75
d)2x-1/4-4-6≤1
x2-1/4-4-6≤1
2x≤11 1/4
x≤5,625
1/3x-x=-2
-2/3x=-2
x=3
b)-14x-7=4
-14x=11
x=-11/14
c)-3/4x=2/4
x=-2/3
zad2
a)
-45x-3x≥-9
-48x-3x≥-9
x≤9/48
b) 5x>0
c) -0,3x-0,6-0,6+0,9>0,1x
-0,4x>0,3
x>0,3: (-o,4)
x>-0,75
d)2x-1/4-4-6≤1
x2-1/4-4-6≤1
2x≤11 1/4
x≤5,625
a)⅓x-x=-2
-2/3x=-2 /*3
-2x=-6/:(-2)
x=3
b)-14x-7=4
-14x=4+7
-14x=11/:(-14)
x=-11/14
-2/3x=-2 /*3
-2x=-6/:(-2)
x=3
b)-14x-7=4
-14x=4+7
-14x=11/:(-14)
x=-11/14
1 a) 1/2x+2=x
1/2x-x=-2
-0,5x=-2 /*(-2)
x=4
b) -7(2x+1)=4
-14x-7=4
-14x=11 /:(-14)
x= -11/14
c)1/4x-x-1/4=1/4
-3/4x=2/4 /*(-4)
3x=-2 /:3
x=-2/3
1/2x-x=-2
-0,5x=-2 /*(-2)
x=4
b) -7(2x+1)=4
-14x-7=4
-14x=11 /:(-14)
x= -11/14
c)1/4x-x-1/4=1/4
-3/4x=2/4 /*(-4)
3x=-2 /:3
x=-2/3